Psychological reactions during competitive season and association with sleep among Norwegian junior elite athletes - Moen, F.; Hrozanova, M.; Myhre, K.; Klöckner, C. (International Journal of Applied Sports Sciences, 2018)
The current study investigated whether athletes with negatively charged psychological reactivity that includes worry and negative affect experience more sleep disturbance in comparison with athletes whose psychological reactivity involves positive affect. Objective sleep monitoring for a period of 3-4 months was utilized in 32 junior elite athletes. Athletes completed the Positive and Negative Affect Scale, and the Penn State Worry Questionnaire before and after the sleep-monitoring period. Results showed changes and disturbances in sleep as a result of a specific psychological reactivity involving high worry and negative affect. On the other hand, positive affect was associated with normal sleep/wake patterns.